1985
DOI: 10.1177/000992288502400307
|View full text |Cite
|
Sign up to set email alerts
|

An Intervention to Improve Follow-up of Patients with Otitis Media

Abstract: We evaluated the effects of an educational intervention and telephone reminders on compliance with medication-taking and appointment-keeping for children with otitis media. During an initial interview we examined parents' health beliefs and other factors associated with compliance in our outpatient setting. The children were then systematically assigned to one of five study groups (G1-5). Parents in G1 received an educational session with a nurse and two follow-up telephone reminders. Parents in G2 received on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0
1

Year Published

1988
1988
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(8 citation statements)
references
References 16 publications
0
7
0
1
Order By: Relevance
“…The value of appointment reminder systems is also supported by prior research, which shows that such systems increase the frequency of follow-up visits. 9,14 Several important factors were associated with missed well-child visits: parents' depressive symptoms, transportation difficulties, being older and employed, and having private (vs public) health insurance. The relationship between missed wellchild visits and parents' depressive symptoms (seen in one fifth of our parents) is particularly noteworthy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The value of appointment reminder systems is also supported by prior research, which shows that such systems increase the frequency of follow-up visits. 9,14 Several important factors were associated with missed well-child visits: parents' depressive symptoms, transportation difficulties, being older and employed, and having private (vs public) health insurance. The relationship between missed wellchild visits and parents' depressive symptoms (seen in one fifth of our parents) is particularly noteworthy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, a study of 4669 patients (not necessarily children) from an urban family practice residency clinic found the following factors to be associated with appointment keeping: older age, Asian or white race/ethnicity, private or managed care insurance, longer distances to travel to the clinic, and appointments scheduled for the day on which they contacted the clinic. 3 Factors that have been associated with visit noncompliance include male gender, 4 divorced/separated or single status, 4 younger age, 5 lower socioeconomic status, 6 unemployment, 7 alcohol or substance abuse, 7 parental psychiatric disorder, 8 absence of telephone reminders, 9 having no health insurance or being insured through medical assistance, 5,10 and having appointments that might evoke embarrassment or fear (eg, psychiatry or gynecology appointment). 4 One study found that provision of a taxicab voucher to pregnant, low income women resulted in a 22% increase in compliance with attending the initial prenatal visit.…”
mentioning
confidence: 99%
“…Studies of potential predictors of follow-through in the general health care setting have shown relationships between compliance and patient satisfaction (Cameron, 1996;Chang, Mayo, & Omery, 2002;Lee, Back, Block, & Stewart, 2002), patients' expectations and whether expectations were met (Gourash, 1978;Kravitz et al, 1996;Vickery & Lynch, 1997), quality of the health care provider-client communication (Fleming, Skochelak, Curtis, & Evans, 1988;Lipkin, 1996;Nelson et al, 1991), and help-seeking behaviors (Casey et al, 1985;Roberts, 1988). Follow-through depends on a complex array of factors that center on the caller, including perceived vulnerability, prior experiences, and acquired knowledge (Cameron, 1996;Kravitz et al, 1996;Vickery & Lynch, 1997).…”
Section: Factors Associated With Following Medical Advicementioning
confidence: 99%
“…Pediatric studies have demonstrated that computergenerated telephone messages can be used successfully to increase immunization rates among preschool children, 29,30 and reminder calls to Medicaid families have been shown to increase well-child screening and to be cost-effective. 31 In addition, follow-up calls in a clinic setting 32 or after emergency department visits 33 have been shown to increase compliance with discharge instructions and follow-up appointments.…”
Section: Commentmentioning
confidence: 99%